The impact of positive psychological personalities on employee's attitude and turnover intention - Chaichi, Kamelia *; Dahlia, Z.; Yuhanis, A. A.; Leong, Mei Kei * (IJICC, 2020)
The hospitality and tourism industry is recognised as a potential service sector in contributing to the Malaysian economy and thoroughly associated with the hotel industry to sustain economic growth. One of the most significant problems for hotel managers is employee turnover. The issue of high voluntary turnover is a matter of grave concern at the national level that it is poorly affecting Malaysia's competitiveness. The present research investigates the impact of positive psychological personality traits in predicting employee's attitude towards the hotel industry and, consequently, reducing turnover intention. Data were collected from hotel employees in Malaysia (n = 200) and analysed using partial least structural equation modelling (Smart-PLS). Specific findings reveal that employee resilience, hope, and optimism increase employee's positive attitude towards the hotel industry and consequently reduce the turnover intention. This study has important implications for hotel managers interested in the determinants of employees' positive attitude towards hotels and employees' turnover intention in the hotel industry in Malaysia.